More than just a crib: Assessing the prevalence of partnerships between Cribs for Kids and children’s hospitals in the United States - Aysha Jawed (BioSocial Health Journal)
Introduction: Cribs for Kids is a national organization with a mission to reduce sudden infant death syndrome (SIDS) and sudden unexpected infant death (SUID) nationwide through adaptation of best practices in infant safe sleep, community engagement, and increased access to resources in assuring infant safety during time of sleep. One integral partnership that enables Cribs for Kids to cast a wider net in yielding the potential to reach many more infants and their families across the country involves attainment of hospitalwide certification by Cribs for Kids across both academic and community healthcare systems that provide care to infants for up to one year of age. Methods: However to date, the prevalence of these partnerships remains unclear. It follows that the present study sought to uncover this prevalence across the nation. Utilizing the U.S. News and World Report, the researcher acquired a random sample of 110 children’s hospitals. Next utilizing the map locator of hospitals certified at the Gold, Silver and Bronze levels by Cribs for Kids on the organization’s website, prevalence of presence and level of certification was ascertained across this sample of children’s hospitals. Results: Notably, the vast majority of this sample (n=78) had not attained hospitalwide certification with Cribs for Kids. Among the hospitals that had attained certification, there was substantial variation across levels based on a range of health promotion and community engagement practices. Conclusion: Recommendations for harnessing the potential of this collaboration are presented to inform directions in examining these partnerships as a point of intervention for future planning considerations across community engagement and health promotion practices surrounding SIDS reduction.